2014
DOI: 10.1186/1471-2474-15-367
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of posterior lumbar interbody fusion and transforaminal lumbar interbody fusion: a literature review and meta-analysis

Abstract: BackgroundWe compared the perioperative results and complications associated with PLIF and TLIF, and collected evidence for choosing the better fusion method.MethodsA literature survey of the MEDLINE and EMBASE databases identified 7 comparative observational studies that met our inclusion criteria. Checklists by Cowley were used to evaluate the risk of bias of the included studies. A database including patient demographic information, perioperative results, and complications was established. The summary odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 45 publications
(45 reference statements)
3
58
1
Order By: Relevance
“…Modern posterior lumbar interbody fusion (PLIF) is a recognised technique for achieving lumbar fusion [20][21][22]. It involves the insertion of paired lordotic cages into the intervertebral disc space combined with posterior pedicle screw and rod instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Modern posterior lumbar interbody fusion (PLIF) is a recognised technique for achieving lumbar fusion [20][21][22]. It involves the insertion of paired lordotic cages into the intervertebral disc space combined with posterior pedicle screw and rod instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis performed by Zhang and colleagues reported that variations in open approaches to the posterior lumbar interbody space can influence the rate of unintended durotomy. 46 Specifically, transforaminal lumbar interbody fusion (TLIF) procedures had a significantly lower durotomy rate as compared with posterior lumbar interbody fusion (PLIF), which is a more medial approach. 46 However, one drawback to making interpretations based on literature reviews is that lumbar surgical approaches and complication rates are evaluated based on a heterogenic population and multiple studies; there is a lack of randomized clinical trials and thus a high reliance on retrospective studies.…”
mentioning
confidence: 99%
“…46 Specifically, transforaminal lumbar interbody fusion (TLIF) procedures had a significantly lower durotomy rate as compared with posterior lumbar interbody fusion (PLIF), which is a more medial approach. 46 However, one drawback to making interpretations based on literature reviews is that lumbar surgical approaches and complication rates are evaluated based on a heterogenic population and multiple studies; there is a lack of randomized clinical trials and thus a high reliance on retrospective studies. 46 Minimally invasive spine surgery (MISS) refers to a modification of the traditional approach that minimizes muscle manipulation, soft tissue dissection, pain, and blood loss.…”
mentioning
confidence: 99%
“…The benefits of the TLIF over the PLIF is the ability to perform the interbody fusion with less retraction and manipulation of the neural elements and ability to place larger cage. The TLIF approach maintains important midline ligaments [73,[76][77][78].…”
Section: Tlifmentioning
confidence: 99%